2004
DOI: 10.1186/1751-0147-45-69
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cobalt and Copper Levels in Lambs in Norway

Abstract: Sivertsen T, Plassen C: Hepatic cobalt and copper levels in lambs in Norway. Acta vet. scand. 2004, 45, 69-77. -Cobalt and copper concentrations were measured in 599 lamb livers collected at slaughter from 58 sheep flocks in 6 different parts of Norway in 1993. Information about pasture, additional feeding and mineral supplements in the flocks was obtained through a questionnaire. Average hepatic levels of cobalt in the lamb flocks varied from <0.003 to 0.22 µg/g ww, and of copper from 5 to 240 µg/g ww. Flocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The results suggest that elevated copper concentrations in the livers of some lambs were likely unrelated to their grazing location. In a study involving 599 lambs grazing in six different areas across Norway, the average hepatic copper concentration varied from 5 to 240 mg/kg (ww) (corresponding to 15–750 mg/kg [dw], with 32% dry weight) (Sivertsen and Plassen 2004 ). This was in sheep herds, with no expected copper poisoning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggest that elevated copper concentrations in the livers of some lambs were likely unrelated to their grazing location. In a study involving 599 lambs grazing in six different areas across Norway, the average hepatic copper concentration varied from 5 to 240 mg/kg (ww) (corresponding to 15–750 mg/kg [dw], with 32% dry weight) (Sivertsen and Plassen 2004 ). This was in sheep herds, with no expected copper poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…This was in sheep herds, with no expected copper poisoning. In Sivertsen and Plassen ( 2004 ), one sheep herd grazed in an area close to Melbu (Sortland, in Vesterålen municipal, Nordland county), the mean hepatic copper concentration in this herd was 57 (5–230) mg/kg (ww) (corresponding to 178 (15–720) mg/kg [dw], with 32% dry weight). These results further strengthen the assumption that the hepatic copper concentrations found in sheep grazing on Melbu (245 mg/kg on range, 242 mg/kg outside range and 218 mg/kg unknown grazing area [dw]), was independent of the grazing area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most widely spread TM deficiency is with Cu [17]. In a study assessing Cu deficiency in grazing sheep [18], it was found that serum and liver Cu content were not in the normal physiological range (7-24 µmol/L and 10-120 mg/kg fresh matter for serum and liver Cu concentration, respectively [19]), even though the Cu content of the grazed herbage (8.61 and 9.26 mg/kg DM for two analyzed pastures) was within the range to cover nutritional requirements for sheep (5-10 mg/kg DM) [5]. The low Cu absorption was mostly due to the high Mo content (>11 mg/kg DM) of the grass [15,18].…”
Section: Trace Mineral Deficiency In Ruminantsmentioning
confidence: 99%